Pengaruh Pemberian Reward dan Punishment terhadap Motivasi Kerja Karyawan pada Dealer BMW Astra HR. Muhammad Surabaya - Estee Lauder Santoso; Emilia Pranata; Iswati Iswati; Siti Aisah (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research wants to know more about "EFFECT OF REWARD AND PUNISHMENT ON EMPLOYEE'S WORK MOTIVATION" in accordance with the main problem, namely the effect of reward and punishment on PT BMW Astra Surabaya's employee motivation. The background for this research is that there are many employees who feel they are not being cared for in their maximum performance and there are still some employees who do not comply with the regulations that have been made. The purpose of this study was to find out: Is the effect of giving rewards and punishments on employee motivation to increase and discipline the performance of existing employees. The method used in this study is a quantitative method that aims to measure the work performance of existing employees in the provision of rewards and punishments whether it will further build employee performance motivation. Meanwhile, to support this research, it was obtained through library research and questionnaires by distributing questionnaires to several sections of employees. The population in this study were employees of BMW Astra Surabaya. The conclusion from this study is that giving rewards greatly influences the work motivation of BMW employees, because employees will receive rewards when they achieve their goals. Giving punishment also affects the work motivation of BMW Astra HR employees. Muhammad, because employees know how to work with more discipline. The existence of reward and punishment allows employees to have benchmarks in everything they do and maintain integrity with every current employee.